2021
DOI: 10.1371/journal.pone.0245266
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptome, small RNA and degradome sequencing approaches proffer insights into chlorogenic acid biosynthesis in leafy sweet potato

Abstract: Leafy sweet potato is rich in total phenolics (TP) which play key roles in health protection, the chlorogenic acid (CGA) constitutes the major components of phenolic compounds in leafy sweet potato. Unfortunately, the mechanism of CGA biosynthesis in leafy sweet potato is unclear. To dissect the mechanisms of CGA biosynthesis, we performed transcriptome, small RNA (sRNA) and degradome sequencing of one low-CGA content and one high-CGA content genotype at two stages. A total of 2,333 common differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Moreover, plants from the EC16 variety accumulated more CQAs compared to the FS7-6 variety (Fig. 1B), which is in agreement with the ndings of Liu et al, (Liu et al 2021). It could be assumed that the differences in CQAs contents between varieties are due to the genetic heritage of each variety, which probably in uences their ability to resist various environmental stresses that stimulate the enzymatic genes involved in the PPs pathway responsible for CQAs biosynthesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, plants from the EC16 variety accumulated more CQAs compared to the FS7-6 variety (Fig. 1B), which is in agreement with the ndings of Liu et al, (Liu et al 2021). It could be assumed that the differences in CQAs contents between varieties are due to the genetic heritage of each variety, which probably in uences their ability to resist various environmental stresses that stimulate the enzymatic genes involved in the PPs pathway responsible for CQAs biosynthesis.…”
Section: Discussionsupporting
confidence: 91%
“…The CQAs were quanti ed using the method described by Liu et al (Liu et al 2021) with few modi cations. Brie y, 50 mg of each sample was dissolved in 70% ethanol (v/v) followed by water bath (60°C, 1h) and then centrifugation (12000 rpm, 10 min).…”
Section: Determination Of Cqa Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomes enriched with oligo-dT would introduce bias since organelle transcripts do not generally contain a polyA tail [ 97 ]. Based on that, sweet potato rRNA-depletion transcriptome data (SRA: SRR10538086 [ 98 ]) were employed and were mapped to the mitogenome to check the expression.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a triploid tea plant and a diploid tea plant were selected as experimental materials in present experiment to study the key genes of CGA biosynthesis in Camellia sinensis. Liu et al (2021) utilized one low-CGA content and one high-CGA content in sweet potato to dissect the mechanisms of CGA biosynthesis by transcriptome data, and found that expression of HCT and other genes were significantly different in the two phenotypes, and therefore inferred that those genes may be the key gene that controlled the synthesis of sweet potato CGA (Liu et al 2021). Wang et al (2020) used the transcriptome to study the CGA biosynthesis of diploid and tetraploid Lonicera japonica, they found that changes in the expression level of some key genes in the biosynthesis pathway at different growth stages led to changes in the content of CGA (Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%